2015
DOI: 10.1016/j.canlet.2014.10.038
|View full text |Cite
|
Sign up to set email alerts
|

A pathway-based approach for identifying biomarkers of tumor progression to trastuzumab-resistant breast cancer

Abstract: Although trastuzumab is a successful targeted therapy for breast cancer patients with tumors expressing HER2 (ERBB2), many patients eventually progress to drug resistance. Here, we identified subpathways differentially expressed between trastuzumab-resistant vs. -sensitive breast cancer cells, in conjunction with additional transcriptomic preclinical and clinical gene datasets, to rigorously identify overexpressed, resistance-associated genes. From this approach, we identified 32 genes reproducibly upregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 51 publications
4
26
0
Order By: Relevance
“…As a demonstration that PRM can be used to initially verify candidate phosphoproteins, we selected four phosphoproteins: Ral GTPase-activating protein subunit alpha-2 (RALGAPA2), cGMP-dependent protein kinase1 (PKG1), tight junction protein 2 (TJP2), and nuclear transcription factor, X box-binding protein 1 (NFX1). These four proteins showed significant phosphorylation up-regulation in patients with cancer, were previously reported as phosphoproteins, and have been implicated in multiple breast cancer studies (23)(24)(25)(26).…”
Section: Verification Of Phosphorylation Specific To Patients With Camentioning
confidence: 99%
“…As a demonstration that PRM can be used to initially verify candidate phosphoproteins, we selected four phosphoproteins: Ral GTPase-activating protein subunit alpha-2 (RALGAPA2), cGMP-dependent protein kinase1 (PKG1), tight junction protein 2 (TJP2), and nuclear transcription factor, X box-binding protein 1 (NFX1). These four proteins showed significant phosphorylation up-regulation in patients with cancer, were previously reported as phosphoproteins, and have been implicated in multiple breast cancer studies (23)(24)(25)(26).…”
Section: Verification Of Phosphorylation Specific To Patients With Camentioning
confidence: 99%
“…(Mohd Sharial et al, 2012;Takada et al, 2013;Xia et al, 2013;Kawajiri et al, 2015;Nam et al, 2015) has shown success in preclinical models. And the HER2 gene has been established as a valid biological marker for the treatment of breast cancer So far, Small Molecule Tyrosine Kinase Inhibitors of HER2 such as Trastuzumab, Pertuzumab, Lapatinib, Afatinib, AZD8931, AST-1306, AEE-788, CI-1033 (Canertinib), CP-724714, CUDC-101, TAK-285, AC-480 (BMS-599626), PF299804, PF299 (Dacomitinib), EKB-569 (Perlitinib) are on their way to clinical use or undergoing phase trials in aggressive breast cancer (Kumler et al, 2014;Schroeder et al, 2014), being explored for their potential to inhibit EGFR and HER2 tyrosine kinases.…”
Section: Treatment Of Breast Cancermentioning
confidence: 99%
“…However, a major limit of immunotherapy with trastuzumab is the development of drug resistance (Nahta, 2012;Brady et al, 2014;Nielsen et al, 2014;Rimawi et al, 2014;Zang et al, 2014;Nam et al, 2015). WenBai et al (2014) referred, trastuzumab resistance was DOI:http://dx.doi.org/10.7314/APJCP.2015.16.7.2591 Recent Progress in HER2 Associated Breast Cancer -a Review characterized by enhanced invasiveness of breast cancer cells with concomitant EMT and elevated TGF-b signaling (Bai et al, 2014).…”
Section: Trastuzumabmentioning
confidence: 99%
See 2 more Smart Citations